Fabrication of calixarene-grafted bio-polymeric magnetic composites for magnetic solid phase extraction of non-steroidal anti-inflammatory drugs in water samples - Yaacob, Syed Fariq Fathullah Syed; Jamil, Arniza Khairani Mohd; Kamboh, Muhammad Afzal; Wan Ibrahim, Wan Aini; Mohamad, Sharifah (PeerJ, 2018)
Calixarene framework functionalized bio-polymeric magnetic composites (MSp- TDI-calix) were synthesized and utilized as magnetic solid-phase extraction (MSPE) sorbent for the extraction of non-steroidal anti-inflammatory drugs (NSAIDs), namely indoprofen (INP), ketoprofen (KTP), ibuprofen (IBP) and fenoprofen (FNP), from environmental water samples. MSp-TDI-calix was characterized by FT-IR, XRD, FESEM, EDX, VSM and BET analysis, and the results were compared with Sp-TDI and Sp-TDI-calix. To maximize the extraction performance of MSp-TDI-calix decisive MSPE affective parameters such as sorbent amount, extraction time, sample volume, type of organic eluent, volume of organic eluent, desorption time and pH were comprehensively optimized prior to HPLC-DAD determination. The analytical validity of the proposed MSPE method was evaluated under optimized conditions and the following figures of merit were acquired: linearity with good determination coefficient (R2 ≥0.991) over the concentration range of 0.5-500 mg/L, limits of detection (LODs) ranged from 0.06-0.26 mg/L and limits of quantitation (LOQ) between 0.20-0.89 mg/L. Excellent reproducibility and repeatability under harsh environment with inter-day and intra-day relative standard deviations were obtained in the range of 2.5-3.2% and 2.4-3.9% respectively. The proposed method was successfully applied for analysis of NSAIDs in tap water, drinking water and river water with recovery efficiency ranging from 88.1-115.8% with %RSD of 1.6-4.6%.